From Sand and Ash - Harmon, Amy (Lake Union Publishing, 2016)
Italy, 1943--Germany occupies much of the country, placing the Jewish population in grave danger during World War II. As children, Eva Rosselli and Angelo Bianco were raised like family but divided by circumstance and religion. As the years go by, the two find themselves falling in love. But the church calls to Angelo and, despite his deep feelings for Eva, he chooses the priesthood. Now, more than a decade later, Angelo is a Catholic priest and Eva is a woman with nowhere to turn. With the Gestapo closing in, Angelo hides Eva within the walls of a convent, where Eva discovers she is just one of many Jews being sheltered by the Catholic Church. But Eva can't quietly hide, waiting for deliverance, while Angelo risks everything to keep her safe. With the world at war and so many in need, Angelo and Eva face trial after trial, choice after agonizing choice, until fate and fortune finally collide, leaving them with the most difficult decision of all.